Understanding the dual structure of job stress challenge stress and hindrance stress among Gen Z workers - Ignacia Callista; Zamralita Zamralita; Ismoro Reza Prima Putra (Priviet Social Sciences Journal, 2026)
Work-related stress has become a salient issue among Gen Z employees as they enter contemporary workplaces characterized by rapid changes, intensified performance demands, and continuous evaluations. Traditional approaches to occupational stress often conceptualize stress as uniformly negative, overlooking qualitative differences in how job demands are appraised. Drawing on the challenge-hindrance stress framework, this study aimed to provide a descriptive and exploratory overview of challenge and hindrance stress among Gen Z workers in Indonesia. A quantitative cross-sectional design was employed, involving 205 Gen Z employees from various organizational sectors. Data were collected through a self-administered online survey using the Challenge and Hindrance Self-Reported Stress Scale developed by Cavanaugh et al. Reliability analysis demonstrated satisfactory internal consistency, with Cronbach’s alphas of .806 and .721 for challenge and hindrance stress, respectively. The descriptive statistical analysis revealed that challenge stress had a higher mean score (M = 3.47, SD = 0.62), indicating a moderate to high level, whereas hindrance stress showed a lower mean score (M = 2.89, SD = 0.68), reflecting a low to moderate level. These findings suggest that Gen Z employees tend to appraise work-related demands more frequently as challenges that promote learning and growth rather than obstacles that hinder performance. Nonparametric difference testing further indicated that stress perceptions were largely homogeneous across most demographic variables, with education level emerging as the only factor significantly associated with stress. The findings support the relevance of the challenge-hindrance stress framework in understanding Gen Z’s work stress experiences and highlight the importance of promoting challenge stress while minimizing hindrance stress to foster sustainable performance and psychological well-being among young employees.